1998
DOI: 10.1088/0953-4075/31/13/002
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic and geometric laser-induced alignment of molecules in intense laser fields

Abstract: The angular distribution of the ionic fragments from multiphoton dissociative ionization of diatomic molecules shows a pronounced anisotropy. Calculations within the fieldionization, Coulomb explosion model show that the experimental I 2 results (pulses of 50 fs at an intensity of ∼10 14 W cm −2 ) can be explained without invoking reorientation of the molecular axis. The fragments of the lighter H 2 and N 2 molecules, on the other hand, show clear signs of being forced into alignment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
128
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(138 citation statements)
references
References 16 publications
10
128
0
Order By: Relevance
“…Consequently, the molecule ionizes predominantly at R ≈ R C . The fragment ions born out of such a CE usually give rise to an anisotropic angular distribution which favors the direction of the polarization vector of the laser field [18,[25][26][27][28][29][30][31][32][33][34]. Such anisotropic angular distributions are characteristic for a CE based on a dynamic or a geometric alignment mechanism or on a combination of these two.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, the molecule ionizes predominantly at R ≈ R C . The fragment ions born out of such a CE usually give rise to an anisotropic angular distribution which favors the direction of the polarization vector of the laser field [18,[25][26][27][28][29][30][31][32][33][34]. Such anisotropic angular distributions are characteristic for a CE based on a dynamic or a geometric alignment mechanism or on a combination of these two.…”
Section: Introductionmentioning
confidence: 99%
“…The interaction between this induced dipole moment and the E-field amplitude of the laser field pre-aligns the parent molecular axis to the laser's Efield amplitude until the molecular bond stabilizes. Subsequently a Coulomb Explosion occurs after which the ionic fragments recoil direction is parallel to the E-field amplitude of the laser pulse [18,[25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…The work of Tzallas et al [17] provides further evidence that ring opening, induced by strong laser fields, is possible. It therefore seems reasonable to assume that the abovementioned channels are plausible candidates based on the split structure observed in the 70 and 80 m/z range, and the indication in the momentum scaled mass spectrum of NB that the high mass fragments have release momenta consistent with H A number of polarization dependent studies of molecular ionization in the tunnel regime indicate that the ion peak shape is dependent on the amount of geometric or dynamic alignment experienced by the molecule [9,10,12,[45][46][47][48][49][50][51][52]. They generally find suppression of ionization when the polarization is circular, and enhancements of ionization in cases where the polarization is linear, with the CE component emphasized when the laser polarization is collinear with the time-of-flight spectrometer axis.…”
mentioning
confidence: 99%
“…The amount of depletion is a measure of the laser-induced alignment. Using this method, Posthumus et al [26,27] concluded that dynamic alignment dominated for H 2 and geometric alignment dominated for I 2 under a 50 fs laser field.…”
mentioning
confidence: 99%